Safety evaluation of the food enzyme glutaminase from the genetically modified Bacillus licheniformis strain NZYM‐JQ - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme glutaminase (l‐glutamine amidohydrolase EC 3.5.1.2) is produced with the genetically modified Bacillus licheniformis strain NZYM‐JQ by Novozymes A/S. The genetic modifications do not give rise to safety concerns. The production strain met the requirements for the qualified presumption of safety (QPS). The food enzyme is free from viable cells of the production organism and its DNA. The enzyme under assessment is intended to be used in six food manufacturing processes. Dietary exposure was estimated to be up to 0.148 mg TOS/kg body weight per day in European populations. Given the QPS status of the production strain and the absence of concern resulting from the food enzyme manufacturing process, toxicological studies were not considered necessary. A search was made for the similarity of the amino acid sequence to those of known allergens and one match with a pollen allergen was found. The Panel considered that the risk of allergic reactions by dietary exposure cannot be excluded, particularly for individuals sensitised to birch and oak pollen. The Panel concluded that the food enzyme does not give rise to safety concerns under the intended conditions of use.